PENERAPAN MODEL PEMBELAJARAN DIRECT INSTRUCTION BERBANTUAN MEDIA INTELLEGENT STICK TERHADAP KEMAMPUAN KOGNITIF DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS 4 MI KHOIRIYATUSSIBYAN TAHUN PELAJARAN 2025/2026 - Nur Jelita Ananda Fransiska; Supriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics instruction in elementary schools continues to encounter numerous challenges, particularly in enabling students to grasp abstract arithmetic concepts. This often hinders the optimal development of students’ cognitive skills. This study focused on fourth-grade students at MI Khoiriyatussibyan during the 2025/2026 academic year, aiming to examine the impact of integrating the Direct Instruction model with Intelligent Stick media on students’ cognitive development in mathematics. The research involved 20 students and followed a structured process: an initial pre-test, implementation of lessons using the specified instructional model and media, and a post-test upon completion. In addition to testing, data were gathered through classroom observations and documentation. Data analysis was performed using SPSS version 23, incorporating normality tests, Paired Sample T-Tests, and N-Gain calculations. Findings revealed a notable improvement in student performance, with average scores rising from 4.80 on the pre-test to 8.95 on the post-test. Statistical analysis yielded a significance value of 0.002 well below the 0.05 threshold indicating a strong effect, while the N-Gain score of 0.79 fell within the high improvement category. These results demonstrate that the Direct Instruction model, when supported by Intelligent Stick media, effectively enhances students’ understanding of mathematical concepts and positively influences their cognitive growth.